The Role of Endoscopic Ultrasound in Primary Pancreatic Lymphoma Presented with Acute Pancreatitis: A Case Report - Abedi, Seyed Hassan; Ahmadzadeh, Alireza; Nikmanesh, Ali; Mohammad Alizadeh, Amir Houshang (JOP. Journal of the Pancreas, 2014)
Context Primary pancreatic lymphoma (PPL) is rare but manageable malignant tumor of the pancreas which may be confused with pancreatic adenocarcinoma. Case report We report a 38 year-old smoker man with IVDA and history of B (inactive carrier), C (Ia genotype) hepatitis and negative for HIV admitted to our hospital because of nausea, vomiting, epigastric and RUQ pain as a result of long period of alcohol consumption. Due to high amount of amylase (480 U/L) and lipase (326 U/L) Pancreatitis was diagnosed. Four days after admission CT was done that showed enhancement a large tumor of the head of the pancreas. Endoscopic ultrasound (EU) revealed diffusely enlarged of pancreas. There was a mixed echoic mass lesion 37-50 mm at the head of pancreas (R/O walled off necrosis) with adhesion to portal vein and SMV. On the other hand the CBD was 9 mm. Abdominal MRI and MRCP for patient was done. The intra-hepatic bile ducts, main hepatic ducts, CHD and CBD were mildly dilated and displaced to the right side by a large lobulated mass (160×112×130 mm) of pancreatic head with low signal intensity on T1W images and high intensity on T2W images. we did EUS-FNA and there was a mixed echotic lesion (38-40 mm) adhered to head of pancreas with invasion to portal vein, SMA and SMV. The diagnosis of pancreatic lymphoma was established by immunohistochemical study and the assessment of the neoplastic cells revealed B cell lymphoma phenotypes. Conclusion Herein we present an interesting 38 year- old man with pancreas head tumor. Primary pancreatic lymphoma is almost never suspected clinically. It is usually diagnosed by imaging and histological methods. Image: Enlarged pancreas and echoic mass lesion.